Physical Activity and Health Related Quality of Life Among Non-Academic Staff of a University - Arimi Fitri Mat Ludin,; Nor Azwani Mohamed Nor,; Syamimi Omar,; Siti Nor Ismalina Isa,; Rituparna Ghoshal,; Mohd Zul Amin Kamaruddin, (Penerbit UKM, 2015)
Literature data on association between physical activity (PA) and health related quality of life (HRQoL) in non-clinical adults population are still limited. Thereby, the objective of this study was to evaluate the association between PA and HRQoL among the non-academic staff serving the Faculty of Health Sciences (FSK), Universiti Kebangsaan Malaysia (UKM), Kuala Lumpur (KL). In this cross sectional study, 105 non-academic staffs aged between 18 to 60 years were recruited. Self-administered questionnaires (Malay version of the International Physical Activity Questionnaire and World Health Organisation Quality of Life-Brief Version) were administered among the participants. Mann Whitney test and Spearman’s rho correlation were employed for the statistical analysis using SPSS version 22.0 Majority of participants (72.4%) demonstrated high PA scores of ≥ 3000 MET-minutes/week. PA scores between genders was not statistically significant (p = 0.137). However, total PA score of support staffs (median = 9039.0, IQR = 15811.00) was significantly higher compared to staffs in management and professional group (median = 4329.0, IQR = 4189.00). The mean(SD) self-perceived HRQoL score was 3.4 (0.76). There were no significant correlation between PA and all domains of HRQoL such as physical health, psychological, social relationship and environmental domains (Correlation coefficient, ρ = -0.108, 0.003, -0.023, 0.026 respectively) with p = 0.273, 0.978, 0.818, 0.794 respectively. Majority of non-academic staffs of FSK, UKM engaged in high physical activity. The PA levels of support staffs were significantly higher than management and professional staffs. However, there was no statistically significant correlation observed between PA and domains of HRQoL.